Examen especial al rubro documentos y cuentas por cobrar clientes relacionados de la compañía “Entre Ríos” s.a. de la ciudad de Loja, período enero - septiembre del 2013 - Soto Montero, Maritza del Rocio (2014)
The song "SPECIAL CONSIDERATION TO ITEM DOCUMENTS AND ACCOUNTS RECEIVABLE CUSTOMER RELATED COMPANY" BETWEEN RIVERS "SA Loja CITY, JANUARY - SEPTEMBER 2013 "was done as a requirement for obtaining the degree of Engineer in Accounting and Auditing; also the company "Entre Rios" SA presented in the Statement of Financial Position a high value item and Accounts Receivable Documents Related Customers, being necessary to do a special test to detect failures, errors or omissions in the management of this area and contribute results to optimize the internal control the organization. The research was developed foresaw the approach of objectives which were fulfilled chronologically, so that internal control was assessed by the use of questionnaires with to examine the risk and to select tests, qualifying the reasonableness of the balance shown in the Statement of Financial Position; compliance testing and substantive testing was applied; finally the report of the Special Review was developed with respective comments, conclusions and recommendations At the end of the work has been concluded that the information contained in the statement of financial position is vital to encounter errors every attempt at progress is unsuccessful reason, the entity must increase a manual of policies that lead to correct application of the accounting system; addition to procedures for the recovery of outstanding securities is put in place because it depends on the economic stability of the institution; which should be conducive to implementing them.